Self-Gravitating Fluid Sphere with Specified Equation of State: Spherically symmetric solutions and properties (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper provides spherically symmetric solution of Einstein’s field equations for the perfect fluid with equation of state p = a, where a [0, 1] has been obtained taking suitable choice of g11 or g44 (e.g. ). Many previously known solutions are contained herein as a particular case. Various physical and geometrical properties have been also studied.